2006
DOI: 10.1063/1.2208907
|View full text |Cite
|
Sign up to set email alerts
|

A constitutive model for a uranium-niobium alloy

Abstract: A constitutive model that includes the effects of elasticity, crystal reorientation (twinning or detwinning), phase transformations, and plasticity is presented. The model is applied to a uranium-6wt% niobium (U-6Nb) alloy, which is known to exhibit the shape memory effect. The inelastic strains for phase transformation and reorientation are based on the material’s phase diagrams. The model captures the effects of martensitic transformation and reorientation; both of the phenomena are coupled with the alloy’s … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 11 publications
0
13
0
Order By: Relevance
“…The power-law viscoplasticity was first introduced in [58,59]. Strength σ p y = σ 0 A T (T) is determined at 0.2% strain, where σ 0 is athermal strength.…”
Section: Kinematics-based Construction Of Hall-petch Relationmentioning
confidence: 99%
“…The power-law viscoplasticity was first introduced in [58,59]. Strength σ p y = σ 0 A T (T) is determined at 0.2% strain, where σ 0 is athermal strength.…”
Section: Kinematics-based Construction Of Hall-petch Relationmentioning
confidence: 99%
“…In this construction, the model captures diffusional flow, power-law creep and plasticity. It is worth mentioning that similar power-law expressions have already been used for metals 23 24 and frictional materials 25 . Elastic material properties complete the constitutive description.…”
Section: Resultsmentioning
confidence: 99%
“…However a careful analysis of the experimental results showed that the absence of the elastic precursor was not due to small differences in elastic and plastic wave velocities, hence the lack of a precursor was unexplained. Field et al (2001), Jackson (1976), Zubelewicz et al (2006) and Cady et al (2006) have studied U-6Nb extensively. U-6Nb twins and twinning dramatically reduces the overall shear stress.…”
Section: Introductionmentioning
confidence: 99%